Development of Three Part Cards Montessori Learning Media on Biodiversity for Grade X Students at SMAN 5 Balikpapan - Vila Wahyu Ardila Visyam; Sonja V.T Lumowa; Yusak Hudiyono; Daniel Tarigan; Lambang Subagyo; Abdul Hakim; Elsje Theodora Maasawet; Vandalita M.M Rambitan (Postgraduate, University of Mataram, 2026)
This study aimed to develop and evaluate the Three Part Cards Montessori learning media for teaching Biodiversity to tenth- grade students at SMAN 5 Balikpapan. The development followed the 4D Model (Define, Design, Develop, Disseminate), including validation by experts, practical trials and effectiveness testing. Data were collected through expert assessments, student responses, and learning outcomes including critical thinking skills. The result showed that the Three Part Cards Montessori media was feasible, practical and effective. Expert Validation scores were high, students responded positively, and significant improvement was observed in students learning outcomes and critical thinking abilities. This study suggests that Three Part Cards Montessori is a promising alternative learning media to enhance conceptual understanding and critical thinking in biology education